2020
DOI: 10.13075/mp.5893.00921
|View full text |Cite|
|
Sign up to set email alerts
|

2-naphthylamine toxicity

Abstract: In the past, 2-naphthylamine (2-NA) was used for the production of azo dyes, as an antioxidant in the cable industry and in the rubber industry. Despite the fact that 2-NA is not produced on an industrial scale, it is still used in small quantities as a model bladder carcinogen in laboratories, and also for sewage control, water analysis and oxytocinase assays. In addition, it is detected in the air in coke ovens, where it is formed as one of the pyrolysis products. The main aim of this work is to provide an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
4
1
2
Order By: Relevance
“…The lethal doses 50 (LD50) of NAP to rats was indicated by experimental studies at 727 mg/kg. The carcinogenicity of NAP was investigated through distinct exposure routes, including oral administration, subcutaneous injections, and intraperitoneal injections [2]. Thus, the intragastric administration of NAP is an effective approach for animal poisoning.…”
Section: Chemicals Animals and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The lethal doses 50 (LD50) of NAP to rats was indicated by experimental studies at 727 mg/kg. The carcinogenicity of NAP was investigated through distinct exposure routes, including oral administration, subcutaneous injections, and intraperitoneal injections [2]. Thus, the intragastric administration of NAP is an effective approach for animal poisoning.…”
Section: Chemicals Animals and Study Designmentioning
confidence: 99%
“…2-naphthylamine (NAP), containing two fused aromatic rings, is referred to as a kind of polycyclic aromatic hydrocarbon (PAH) [1]. Occupational exposure to 2-naphthylamine (NAP) primarily takes place in the laboratories employing NAP for cancer research; the workers are exposed to NAP from fumes after pyrolysis and from the metabolic process of nitric polycyclic aromatic hydrocarbons in dye and rubber industrial production [2]. Notably, recent research found that cigarettes, including e-cigarette smoke, and the fumes from heating food oils, are the main sources of general population exposure [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…jako substancja modelowa w badaniach nad rakiem. Do narażenia na 2-NA może dojść podczas pirolizy związków organicznych zawierających azot, a także podczas ogrzewania olejów spożywczych i poprzez narażenie na dym tytoniowy [14,15].…”
Section: Wstępunclassified
“…Według Centralnego Rejestru Danych o Narażeniu na Substancje, Mieszaniny, Czynniki i Procesy Technologiczne o Działaniu Rakotwórczym lub Mutagennym w Polsce w 2017 r. na działanie 2-NA i jej soli było narażonych 208 osób (201 na 2-NA i 7 na jej sole). Osoby narażone pracowały w laboratoriach uczelnianych, instytutach, inspekcjach, urzędach kontrolnych, laboratoriach zakładów farmaceutycznych i w zakładzie produkującym farby [15,17].…”
Section: Wstępunclassified